Training of basketball tactics and tactics consciousness - Kai, L. (Frontiers in Sport Research, 2020)
Tactical training has always been an important part of basketball training.In the formal competition, athletes can give full play to their technical level and tactical level only if their physical tactical actions and mental tactical awareness are developed. This paper first briefly introduces the characteristics of basketball, then probes into the content and key points of basketball tactical training from the perspective of basic cooperation, and finally expounds the cultivation strategies of individual tactical awareness and team tactical awareness.